2022
DOI: 10.1371/journal.pone.0273340
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab, netakimab, and baricitinib in patients with mild-to-moderate COVID-19: An observational study

Abstract: Objective The aim of the study was to assess inflammatory markers and clinical outcomes in adult patients admitted to hospital with mild-to-moderate COVID-19 and treated with a combination of standard-of-care (SOC) and targeted immunosuppressive therapy including anti-IL-17A (netakimab), anti-IL-6R (tocilizumab), or JAK1/JAK2 inhibitor (baricitinib) or with a standard-of-care therapy alone. Methods The observational cohort study included 154 adults hospitalized between February and August, 2020 with RT-PCR-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
0
16
0
1
Order By: Relevance
“…Interestingly, anti-IL-17 treatment with netakimab or secukinumab in patients with severe COVID-19 decreased the incidence of pulmonary embolism, suggesting that IL-17 is a key player contributing to this disease complication 40,41 which is in line with the reported pro-coagulant and pro-thrombotic effects of IL-17 42 . The treatment of patients with moderate COVID-19 with netakimab significantly reduced systemic inflammation and improved clinical disease, decreasing the length of stay and mortality 43 . Altogether, these results suggest that anti-IL-17 treatment efficacy is dependent on the severity of the disease, being more effective in COVID-19 cases where the inflammation status is more intense.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, anti-IL-17 treatment with netakimab or secukinumab in patients with severe COVID-19 decreased the incidence of pulmonary embolism, suggesting that IL-17 is a key player contributing to this disease complication 40,41 which is in line with the reported pro-coagulant and pro-thrombotic effects of IL-17 42 . The treatment of patients with moderate COVID-19 with netakimab significantly reduced systemic inflammation and improved clinical disease, decreasing the length of stay and mortality 43 . Altogether, these results suggest that anti-IL-17 treatment efficacy is dependent on the severity of the disease, being more effective in COVID-19 cases where the inflammation status is more intense.…”
Section: Discussionmentioning
confidence: 97%
“…When acting as immune regulator, IL6 is able to work on both the innate and acquired arms of the system: on one side, it can de-regulate natural killer and CD8 + T cell responses, thus reducing antiviral defenses; on the other side, it can interfere with acquired immune responses by promoting B cell differentiation toward antibody-producing plasma cells and by regulating CD4 T cell differentiation toward Th2 and Th17 lymphocytes [ 98 , 100 , 101 , 102 , 103 ].…”
Section: Currently Validated Biomarkers In Clinical Practicementioning
confidence: 99%
“…Since the beginning of the pandemic, different observational studies and clinical trials have investigated the effectiveness of IL6 signaling inhibitors in preventing ARDS and mortality in SARS-CoV-2-positive patients. In this context, the most studied drug is tocilizumab, a recombinant humanized monoclonal antibody directed to IL6 receptor alpha [ 101 , 107 , 108 ]. Recent meta-analyses, including the most recently published results of randomized clinical trials performed using a random-effects model to pool the results of the clinically heterogeneous trials, found that tocilizumab administered along with the standard of care therapy was able to reduce both 28-day mortality index and the need of mechanical ventilation and ICU admission, as well as to shorten the time to discharge [ 97 , 102 , 109 , 110 ].…”
Section: Currently Validated Biomarkers In Clinical Practicementioning
confidence: 99%
“…For later presentations, anti-inflammatory agents (e.g. tocilizumab or baricitinib) are well established [196][197][198] and further stratification may allow selection of patients requiring treatment with various other immunomodulatory agents at later stages of disease. In MIS patients, anti-inflammatory strategies can be used, although with some differences, and intravenous immunoglobulin and thromboprophylaxis with low-dose aspirin is also considered [199][200][201][202][203][204][205].…”
Section: Delayed Acute Systemic Hyperinflammatory Response: Mismentioning
confidence: 99%